Clumped isotope constraints on the origins of reservoir methane from the Barents Sea. Issue 2 (2022) - Thiagarajan, Nivedita; Pedersen, Jon Halvard; Brunstad, Harald; Rinna, Joachim; Lepland, Aivo; Eiler, John
No abstract available